Validated RP-LC Methods for Investigating the Degradation Behavior of Acefylline: Application for Analysis in Two Binary Mixtures - EL-Houssini, Ola M.; Zawilla, Nagwan Hamdi; Mohammad, Mohammad Abdul-Azim (Current Pharmaceutical Analysis, 2021)
Background: Acefylline (Acef) is a derivative of theophylline that has bronchodilator effects. Two binary mixtures were marketed for Acef: Acefylline piperazine/ Phenobarbitone (Acef- P/Phen) and Acefylline heptaminol/ Cinnarizine (Acef-H/ Cinn). To our knowledge, none of the reported methods had the capacity to determine Acef in its binary mixture in the presence of its degradation products and potential impurity theophylline (Theo). Methods: Two validated RP-LC methods were established for the determination of Acef-P/Phen and Acef-H/ Cinn, in the presence of Acef degradation products and its’ potential impurity Theo. A complete study of the forced acidic, alkaline, and oxidative degradation of Acef was presented. The methods were based on LC separation on RP C18 columns using isocratic and gradient elution for Acef-P /Phen and Acef-H /Cinn mixtures, respectively. Different chromatographic conditions were examined and optimized. Results: Linear responses were attained over concentration ranges of 75-500/15-1000 μg/mL and 100- 1000 /50-500 μg/mL with mean percentage recoveries of (100.72±1.23)%/ (99.29±1.12)% and (100.44±1.27)%/ (99.01±0.97)% for Acef-P/Phen and Acef-H /Cinn, respectively. ICH guidelines were used for methods validation and all the parameters were found to be acceptable. Conclusion: The methods showed to be accurate, precise, and specific for the analysis of Acef-P/Phen and Acef-H /Cinn in drug substance, drug product, and in laboratory prepared mixtures in the presence of Theo and up to 50% of degradation products. The structures of the main degradation products and the expected degradation pathway were suggested using the MS data.
Keywords: forced degradation study